Poziom wiedzy młodzieży u progu pełnoletności na temat profilaktyki chorób nowotworowych. Prezentacja wybranych wyników z badania = The level of knowledge of youth on the threshold of adulthood on cancer prevention. Presentation of selected results from the research - Grzegorczyk, Milena; Kita, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Health promotion is an essential task for both the health sector and education institutions. Interested in the topic of health members of the Doctoral Student Research Sociology of Health, Disease and Medicine met the research: "The level of knowledge about cancer prevention and health behaviors among the youth on the threshold of adulthood". The article presents selected results from these research, obtained on the basis of the answers given by the students of secondary schools Zielona Gora in the period from May to June 2016.
Keywords: profilaktyka; młodzież; edukacja zdrowotna; choroba nowotworowa; badania empiryczne; prevention; youth; health education; cancer; empirical research